Discharging of PCM in Various Shapes of Thermal Energy Storage Systems: A Review - Dhaidan, Nabeel; Hashim, Hasan; Abbas, Abdalrazzaq; Khodadadi, Jay; Almosawy, Wala; Al-Mousawi, Fadhel (Journal of thermal science, 2023)
Utilizing the phase change materials in different thermal storage applications attains valuable attention due to the fascinating thermal properties of these materials. The comprehension of the thermal behaviour of phase change materials during the melting and solidification is considered a significant priority in designing the shape of the different containers. In this review, analytical, computational and experimental investigations that address solidification/freezing of phase change materials within thermal energy storage systems are discussed. Emphasis is placed on the role of the shape of adopted containers encompassing planar, spherical, cylindrical and annular vessels. Energy storage for solar thermal applications, waste heat recovery, and thermal management of buildings/computing platforms/photovoltaics has been the topics that benefit from these investigations. For all container shapes, the freezing process is controlled initially by natural convection, and a high solidification rate is observed. Later, the conduction dominates the process, and the freezing rate declines. The temperature and flow of cooling heat transfer fluid affect the solidification process, but the impact of heat transfer fluid temperature is more significant than its flow rate. Also, the freezing time increases with the container’s size and amount of contained PCM. The aspect ratio of the planar and vertical cylindrical cavities substantially influences the discharging time and rate. In contrast, the orientation of the annular cavity has a lower impact on the discharging process.